Structural Activity Relationship Analysis of New Diphenyl PFI-3 Analogues Targeting for the Treatment of Glioblastoma - Dong-Jin Hwang; Chuanhe Yang; Yinan Wang; Hannah Kelso; Satyanarayana Pochampally; Lawrence M. Pfeffer; Duane D. Miller (Pharmaceuticals)
Background/Objectives: Human glioblastoma (GBM) is the most aggressive brain cancer in adults and a highly treatment-refractory malignancy. The overall prognosis for the GBM is extremely poor, with a median survival of 12–14 months after initial diagnosis. Many GBM patients initially respond to the DNA alkylating agent temozolomide (TMZ), but patients often become therapy-resistant, and tumors recur. We previously reported that treatment with PFI-3, which is a small molecule inhibitor of the bromodomain of the BRG1 subunit of the SW1/SNF chromatin remodeling complex, enhanced the sensitivity of GBM cells to TMZ in vitro and in vivo GBM animal models. Our general objective was to perform an SAR study of new diphenyl PFI-3 analogs. Methods: New structural analogs of PFI-3 were developed, synthesized, and tested for their ability to enhance TMZ-induced GBM cell death by ELISA. Results: Following on the enhanced activity of compounds 2a and 2b, new diphenyl PFI-3 analogs with specific structural adjustments were made to better understand the structural requirements to optimize function. Additionally, several new structurally different candidates (e.g., 4a, 4b, and 5) showed much better efficacy in sensitizing GBM cells to TMZ-induced GBM cell death. Conclusions: Four series of PFI-3 analogs (2, 3, 4, and 5) were designed, synthesized, and tested for the ability to sensitize GBM cells to TMZ-induced cell death. Series 2 optimized the A-ring and R-isomer chirality. Series 3 used a 5-membered linker with weak activity. Series 4’s di-phenyl urea compounds showed better bromodomain inhibition. Series 5’s methoxyphenyl-B-ring analogs were exceptionally strong inhibitors.